2010
DOI: 10.2202/1542-6580.2238
|View full text |Cite
|
Sign up to set email alerts
|

A Review of the Water Gas Shift Reaction Kinetics

Abstract: The world's progression towards the Hydrogen economy is facilitating the production of hydrogen from various resources. In the carbon based hydrogen production, Water gas shift reaction is the intermediate step used for hydrogen enrichment and CO reduction in the synthesis gas. This paper makes a critical review of the developments in the modeling approaches of the reaction for use in designing and simulating the water gas shift reactor. Considering the fact that the rate of the reaction is dependent on variou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
154
1
6

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 195 publications
(172 citation statements)
references
References 59 publications
1
154
1
6
Order By: Relevance
“…Due to the vast industrial interest shown in both the FT and WGS reactions ag reat deal of attention has been paid to both. [20][21][22][23][24][25] Despite the significant interesti nt he WGS reaction, kinetic studies of the RWGS reactionh ave so far remainl imited. [26] Kinetic studies for the overall process of CO 2 hydrogenation to hydrocarbons has attracted even less attention with very few studies published.…”
Section: Introductionmentioning
confidence: 99%
“…Due to the vast industrial interest shown in both the FT and WGS reactions ag reat deal of attention has been paid to both. [20][21][22][23][24][25] Despite the significant interesti nt he WGS reaction, kinetic studies of the RWGS reactionh ave so far remainl imited. [26] Kinetic studies for the overall process of CO 2 hydrogenation to hydrocarbons has attracted even less attention with very few studies published.…”
Section: Introductionmentioning
confidence: 99%
“…Generally, two different approaches have been used to develop a suitable kinetic model for the rate of catalytic reactions [5]. Microkinetics modeling explores the detailed chemistry of the reaction.…”
Section: Introductionmentioning
confidence: 99%
“…Prior to the testing it was pressed, crushed, and sieved to the range of 200-300 µm. [13]. Moreover, we performed a blank test in each experiment using a fixed bed of an inert material (SiC)…”
Section: Reaction Proceduresmentioning
confidence: 99%